If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 5)(2x + 3)(3x + 9) = 0 Reorder the terms: (5 + x)(2x + 3)(3x + 9) = 0 Reorder the terms: (5 + x)(3 + 2x)(3x + 9) = 0 Reorder the terms: (5 + x)(3 + 2x)(9 + 3x) = 0 Multiply (5 + x) * (3 + 2x) (5(3 + 2x) + x(3 + 2x))(9 + 3x) = 0 ((3 * 5 + 2x * 5) + x(3 + 2x))(9 + 3x) = 0 ((15 + 10x) + x(3 + 2x))(9 + 3x) = 0 (15 + 10x + (3 * x + 2x * x))(9 + 3x) = 0 (15 + 10x + (3x + 2x2))(9 + 3x) = 0 Combine like terms: 10x + 3x = 13x (15 + 13x + 2x2)(9 + 3x) = 0 Multiply (15 + 13x + 2x2) * (9 + 3x) (15(9 + 3x) + 13x * (9 + 3x) + 2x2 * (9 + 3x)) = 0 ((9 * 15 + 3x * 15) + 13x * (9 + 3x) + 2x2 * (9 + 3x)) = 0 ((135 + 45x) + 13x * (9 + 3x) + 2x2 * (9 + 3x)) = 0 (135 + 45x + (9 * 13x + 3x * 13x) + 2x2 * (9 + 3x)) = 0 (135 + 45x + (117x + 39x2) + 2x2 * (9 + 3x)) = 0 (135 + 45x + 117x + 39x2 + (9 * 2x2 + 3x * 2x2)) = 0 (135 + 45x + 117x + 39x2 + (18x2 + 6x3)) = 0 Combine like terms: 45x + 117x = 162x (135 + 162x + 39x2 + 18x2 + 6x3) = 0 Combine like terms: 39x2 + 18x2 = 57x2 (135 + 162x + 57x2 + 6x3) = 0 Solving 135 + 162x + 57x2 + 6x3 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '3'. 3(45 + 54x + 19x2 + 2x3) = 0 Ignore the factor 3.Subproblem 1
Set the factor '(45 + 54x + 19x2 + 2x3)' equal to zero and attempt to solve: Simplifying 45 + 54x + 19x2 + 2x3 = 0 Solving 45 + 54x + 19x2 + 2x3 = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 4.9x^2+5.25x-20=0 | | 3a+28=5a-4 | | (ab^3)(a^4b^8)= | | -3x-10y=10 | | 4m+mn+28+7n= | | (a^16b^8)(a^5b^5)= | | b^2(3b+n)-n(3b+n)= | | 14f-7=3f | | x(y-5)+z(y-5)= | | 5y^0= | | 101+89+73=(4-2)180 | | 9(x-1)=11(x+4) | | 7y-2(y+4)=7 | | z+107=180 | | 9x^6-45x^5+18x^4= | | x^2+20+x^2+62=180 | | 2(x-3)+5=3(x-11x) | | 23w^4-64= | | 39y^10+9y^6= | | 12p^4a+20p^5a^6= | | 16x^3z+20x^4z^6= | | 2.5x+.5x+11=-1 | | x=(x-8)(x^2+8x+64) | | 5y+6=7y | | -10+3m=17 | | 5(4x+3)-8x= | | 36x^4+4x^3=0 | | -6d=54 | | 8x=3y+11.50 | | 2n+128=180 | | 2n+144=180 | | 24q^2-16q=0 |